1983
DOI: 10.1177/000348948309200122
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids and Anaerobic Microorganisms in the Contents of the Cholesteatoma SAC

Abstract: Organic acids in the contents of the cholesteatoma sac from 28 cases were studied by gas chromatographic technique. Five volatile fatty acids (acetate, propionate, isobutyrate, butyrate and isovalerate) and lactate were detected in large amounts, which may lower the pH of the cholesteatoma content. These acids were considered to be derived from products of anaerobic microorganisms. Therefore, the contents from 12 cases were cultured anaerobically in a glove box. Obligate microorganisms were identified in 92% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…However, this theory was not well grounded at the time and was only a speculation based on their clinical observations. In the 1980s, Iino et al . detected abundant organic acids, including lactate and short‐chain fatty acids, in the keratin debris of cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this theory was not well grounded at the time and was only a speculation based on their clinical observations. In the 1980s, Iino et al . detected abundant organic acids, including lactate and short‐chain fatty acids, in the keratin debris of cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, this theory was not well grounded at the time and was only a speculation based on their clinical observations. In the 1980s, Iino et al 47 detected abundant organic acids, including lactate and short-chain fatty acids, in the keratin debris of cholesteatoma. Moreover, Kaneko et al 40 and Suzuki et al 17 discovered that bone destruction is observed in the vicinity of the ruptured cholesteatoma epithelium, where keratin debris escapes through the epithelial break towards the subepithelial layer.…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobes were isolated from about 50% of the patients with chronic suppurative otitis media [4,6,19,20] and those with infected cholesteatoma [21,22]. The variability in the rate of recovery of anaerobes in various studies may be attributed to differences in geographic locations and laboratory methodologies.…”
Section: Otitis Mediamentioning
confidence: 99%
“…Anaerobes are often isolated from infected cholesteatomas [21,22]. The cholesteatoma can induce bone absorption, which is enhanced by the organic acids produced by anaerobic bacteria [22].…”
Section: Otitis Mediamentioning
confidence: 99%
See 1 more Smart Citation